2004
DOI: 10.1353/eca.2005.0007
|View full text |Cite
|
Sign up to set email alerts
|

Budget Deficits, National Saving, and Interest Rates

Abstract: Brookings Papers on Economic Activity, 2:2004 3. Domestic investment represents the accumulation of assets in a country by both its own residents and foreigners. Net foreign investment is the accumulation of assets abroad by residents less the accumulation of assets in the home country by foreigners. The sum of the two is just the accumulation of assets, by residents, in the home country and abroad. This sum must equal national saving. 104 Brookings Papers on Economic Activity, 2:2004 5. The unified budget is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 111 publications
(39 reference statements)
5
83
1
4
Order By: Relevance
“…Their models yielded a very wide range of estimates, where a statistically significant portion of the tax cut is saved and, of course, a statistically significant portion is consumed. When consumption was measured as a ratio to net income, the decrease in taxes could be associated with a proportional and almost identical increase in consumption as well as with a very small increase (Gale and Orszag 2004). These ambiguous results are only partly compatible with the findings of this paper, as a very huge range of possible consumption responses on tax or income changes indicate that everything is possible -consumers may be forward looking, but they also may be not.…”
Section: Discussionsupporting
confidence: 46%
“…Their models yielded a very wide range of estimates, where a statistically significant portion of the tax cut is saved and, of course, a statistically significant portion is consumed. When consumption was measured as a ratio to net income, the decrease in taxes could be associated with a proportional and almost identical increase in consumption as well as with a very small increase (Gale and Orszag 2004). These ambiguous results are only partly compatible with the findings of this paper, as a very huge range of possible consumption responses on tax or income changes indicate that everything is possible -consumers may be forward looking, but they also may be not.…”
Section: Discussionsupporting
confidence: 46%
“…Some researchers, particularly from developed economies, are of the view that large and persistent fiscal deficits can significantly depress stock prices [5,[14][15][16][17][18]. Geske and Roll [14] used a simple linear regression model and found that the expected directional impact of budget deficits on stock return should be negative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What most can agree upon, however, is that this imbalance will not continue forever. Increasing debt and deficit spending relative to GDP has been shown to increase interest rates (Gale, 2004 andEngen/Hubbard, 2004). "The real question is whether the large-scale borrowing is sustainable."…”
Section: Precarious Balance In Ensuring Future Availability Of Capitamentioning
confidence: 99%